Census of the population 1890 - Occupational groups - Hedström, Peter (Stockholm University, 1999)
This data collection contains information about total population and total number of professionally employed within the principal occupational groups agriculture, industry, commerce, government services and unspecified occupation.

This data collection contains information about total population and total number of professionally employed within the principal occupational groups agriculture, industry, commerce, government services and unspecified occupation.
Folkräkningen 1890 - Yrkesgrupper
Keywords: occupations; yrken; population; befolkning; census data; folkräkningsdata; rural population; landsbygdsbefolkning; urban population; stadsbefolkning; Censuses; Folkräkningar; Employment; Sysselsättning; HISTORY; HISTORIA; History; Historia